PENGARUH KONSUMSI AIR REBUSAN DAUN SIRSAK (Annona muricata linn) TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI WILAYAH DESA MIANGAS KABUPATEN KEPULAUAN TALAUD PROVINSI SULAWESI UTARA - Supriyadi Supriyadi; Helmi Pade; Ronasari Mahaji Putri (Journal of Nursing Care and Biomolecular, 2023)
High blood pressure is a disease that always increases every year, this health problem often attacks the elderly group. One of the treatments for high blood pressure is the use of plants. Soursop leaf (Annona muricata linn) can be an alternative for the treatment of high blood pressure because it contains antioxidants and the working process of potassium ions can lower blood pressure. The purpose of the study was to determine the effect of consuming boiled water from soursop leaves (Annona muricata linn) on blood pressure in elderly people with hypertension in the Miangas Village Area. This research design is pre-experimental, with a one group pretest-posttest design approach. The research population in all elderly people with hypertension grade I and II in Miangas Village, as many as 34 people, obtained a sample of 31 respondents using quota sampling technique. The independent variable of this study was the consumption of boiled water from soursop leaves (Annona muricata linn) and the dependent variable was blood pressure. The research instrument used a sphygmomanometer, a stethoscope, and an observation sheet. Data analysis used marginal homogeneity. The concept of soursop leaf stew using ± 10 grams of soursop leaves is launched with 300 ml of water for 30 minutes to become 100 ml and drunk at 06:00-09:00 WITA. The results showed a change in blood pressure from high blood pressure grades I and II (140-160/90-100 mmHg) to normal (130/80). Statistical tests found that there was an effect of consumption of boiled water from soursop leaves (Annona muricata linn) on blood pressure in the elderly with hypertension in the Miangas Village Region, Talaud Islands Regency, North Sulawesi Province with (p-value 0.000). Suggestions for further research can control the variables of smoking status and gender so that the results of the study will be better.   Keywords: Soursop leaf boiled water; Experiments; Herbs; elderly; High blood pressure